'Light in dark places': exploring qualitative data from a longitudinal study using creative arts as a form of social prescribing. Issue 3 (2nd September 2019) - Redmond, Mark; Sumner, Rachel C.; Crone, Diane M.; Hughes, Samantha
ABSTRACT: Background : This paper draws on a longitudinal study exploring the outcomes of an arts referral programme in General Practice in the South West of England since 2009. It focuses on the qualitative responses of the patient cohort Methods : Using qualitative methods and thematic analysis, this paper explores and considers the responses from n = 1297 participants who provided feedback from an open-ended questionnaire on self-reported benefits of the arts referral programme. Results : Participant reactions demonstrate that the programme provided a range of personal and social benefits rarely considered or explored in comparative studies. The analysis suggests participants were able to self-manage aspects of their health-related conditions, and were able to make progress towards a better physical and/or mental health. Conclusions : The evidence suggests that arts-based referral programmes, have a range of benefits for participants that may not have been fully appreciated. The consequences on self-management requires further investigation.